Factores de riesgo asociados al parto pretérmino en gestantes atendidas en el área de ginecoobstetricia del Hospital General IESS Babahoyo, octubre 2024- mayo 2025. - Arana Rivera, Emiliana Andreina (2025)
Preterm birth, as defined by some authors and organizations, is birth that occurs before 37 weeks of gestation and may vary in categories. This is a significant issue because it is a health problem that brings complications for both the mother and the newborn. Objective: To evaluate the relationship between risk factors and the incidence of preterm birth in pregnant women treated at the IESS Babahoyo General Hospital during the period October 2024-May 2025. Method: The research was descriptive, cross-sectional, and retrospective, based on events that occurred at a specific time in the past. Population: A total of 1602 pregnant women were attended to in the Gynecology-Obstetrics area of the IESS General Hospital Babahoyo, during the period October 2024-January 2025. Sample: 310 medical records of pregnant women was obtained using a finite population statistical formula for data collection. This project will be based on inclusion and exclusion criteria. Results: The results show that 45% of the women are of advanced age, between 36 and 41 years old. 64% come from rural areas, 46% have a secondary education level, 29% have a history of hypertensive disorders, and 40% have problems with amniotic fluid. Conclusion: Sociodemographic, obstetric, and clinical factors all play a significant role in preterm birth risk. Sociodemographic factors most strongly associated with preterm birth include maternal age, education level, and place of residence. Obstetric factors include gestational age, prenatal checkups, and mode of delivery. Clinical factors include hypertensive disorders, premature rupture of membranes, acute fetal distress, and oligohydramnios.